2016
DOI: 10.1080/19440049.2016.1162112
|View full text |Cite
|
Sign up to set email alerts
|

Updated survey of Fusarium species and toxins in Finnish cereal grains

Abstract: The aim of the project was to produce updated information during 2005-14 on the Fusarium species found in Finnish cereal grains, and the toxins produced by them, as the last comprehensive survey study of Fusarium species and their toxins in Finland was carried out at the turn of the 1960s and the 1970s. Another aim was to use the latest molecular and chemical methods to investigate the occurrence and correlation of Fusarium species and their mycotoxins in Finland. The most common Fusarium species found in Finl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 61 publications
6
88
0
1
Order By: Relevance
“…Since in the field, many other factors can influence the appearance of symptoms, we assume that an estimation of the DON content is not possible by visual assessment. Nevertheless, the FG incidences and the DON contents were closely related, which showed that FG was the main DON producer, as observed in other studies with several cereal types (Hietaniemi et al 2016;Lindblad et al 2013). …”
Section: Discussionsupporting
confidence: 58%
“…Since in the field, many other factors can influence the appearance of symptoms, we assume that an estimation of the DON content is not possible by visual assessment. Nevertheless, the FG incidences and the DON contents were closely related, which showed that FG was the main DON producer, as observed in other studies with several cereal types (Hietaniemi et al 2016;Lindblad et al 2013). …”
Section: Discussionsupporting
confidence: 58%
“…Even in Finland, spring cereals have been noted to be more susceptible to fungal infection and mycotoxins formation than winter cereals [19]. Orlando et al [23] identified sowing date as the most important agronomic factor that influences the levels of T-2 and HT-2 toxins in French barley.…”
Section: Resultsmentioning
confidence: 99%
“…The original DNA and toxin concentrations were transformed to logarithmic values in order to obtain a more normal distribution for the values of toxin and DNA concentrations [19]. …”
Section: Methodsmentioning
confidence: 99%
“…These high amounts can be partly explained by the way plots were inoculated since DON amounts in the non-inoculated trial were much lower (data not shown). However, similar or higher DON amounts have already been recorded in Germany, Poland, Japan, the USA or Argentina in non-inoculated fields (Placinta et al 1999;Hietaniemi et al 2016). Therefore, inoculating F. graminearum on the soil surface could mimic conditions encountered during a year of severe infection.…”
Section: Reliability Of the Measured Don Amountsmentioning
confidence: 99%